Effects of livestock grazing on soil nitrogen mineralization on Hulunber meadow steppe, China - Yan, R.; Yang, G.; Chen, B.; Yan, Y.; Xin, X.; Li, L.; Zhu, X. (Czech Academy of Agricultural Sciences, 2016)
Soil nitrogen (N) cycling is an important factor in terrestrial ecosystems, including grasslands. Understanding the effects of grazing on nitrogen cycling in grassland ecosystems is critical for better management and for improving knowledge of the mechanisms underlying grassland degradation and can provide basic information for sustainable development in grassland ecosystems. In this study, in situ incubation in intact soil cores was used to measure seasonal changes in soil nitrogen mineralization and nitrification in the meadow steppe of the Hulunber grasslands of northeastern China. Soil plots were subjected to varying intensities of cattle grazing, and soil characteristics including several aspects of the nitrogen cycle were analysed. The findings demonstrate that soil inorganic N pools and nitrogen mineralization peaked in August and that moderate grazing intensity produced higher seasonal mean net N mineralization (Amin); net nitrogen mineralization rate (Rmin); net ammonification rate (Ramm) and net nitrification rate (Rnit). Seasonal mean net mineralization rate was increased by 6–15% in the lightly and moderately grazed plots (0.34–0.46 AU cow/ha) and by 4–5% in the heavily grazed plots (0.69–0.92 AU cow/ha). Also it was found that soil moisture was significantly positively correlated with inorganic N, Amin, Ramm and Rmin and significantly negatively correlated with Rnit, while soil temperature exhibited the opposite effect. The obtained results demonstrated net nitrogen mineralization and ammonium rates, which were strongly linked to grazing intensity, soil temperature and soil moisture.